INFORMATION TECHNOLOGY FOR THE INTEGRATED ASSESSMENT OF EXPERT COMPETENCY - Olena Lobach; Igor Babych; Elena Persiyanova (Сучасний стан наукових досліджень та технологій в промисловості)
The subject matter of the study is the processes of selecting and assessing the competency of experts. The goal of the study is to increase the objectivity of expert assessment by developing and applying a model and information technology for the integrated assessment of the competency of experts, which will enable selecting experts for participation in expert groups on a high qualitative level. The following tasks were solved: methods and models for assessing the quality and competency of experts were reviewed; a model for the integrated assessment of the competency of experts was developed; an applied information technology for a comprehensive assessment of the competency of experts was designed and implemented in software. The methodology of the study was based on the following methods: methods of heuristic, test and statistical evaluation were used to develop the model for the integrated assessment of the competency of experts; principles of system analysis and methods of object-oriented design were used to develop the applied information technology for the integrated assessment of the competency of experts. The following results were obtained: the problem of assessing the quality of experts was considered; based on the authors’ practical experience and analysis of literature sources, the structural diagram of the properties of experts and their assessment was developed; five main groups of existing methods for assessing the quality of experts were analyzed; existing models of an integrated assessment of the competency of experts were reviewed; a two-stage method for the integrated assessment of the competency of experts was developed by integrating the methods of heuristic, test, and statistical assessment; the main groups of users and functional requirements to the information system for assessing the competency of experts were identified; the database and user interface of the information system were developed; the developed information technology of the integrated assessment of the competency of experts was tested on actual data for selecting an expert group to choose the methodology of project management. Conclusions. The problem of selecting and assessing the competency of experts is one of the most difficult in the theory and practice of expert surveys. It cannot be solved by applying singular methods of assessment; its solution requires that complex methods, including both quantitative and qualitative methods for assessing the competency of specialists, should be applied. The applied information technology was developed for this purpose; it can be used at various enterprises, institutions, and organizations that are interested in automating the process of expert survey and in building quality expert groups.